Transforming ourselves, transforming the world : justice in Jesuit higher education - Combs, Mary Beth; Schmidt, Patricia Ruggiano, 1944- (Fordham University Press, 2013)
This book is an essay collection that articulates how Jesuit colleges and universities create an educational community energized to transform the lives of its students, faculty, and administrators - and to equip them to transform a broken world. The essays are rooted in Pedro Arrupe's ideal of forming men and women for others and inspired by Father Peter-Hans Kolvenbach's October 2000 address at Santa Clara in which he identified three areas where the promotion of justice may be manifested in our institutions: formation and learning, research and teaching, and our way of proceeding. Using the three areas laid out in Fr. Kolvenbach's address as its organizing structure, this volume addresses the following challenges: How do we promote student life experiences and service? How does interdisciplinary collaborative research promote teaching and reflection? How do our institutions exemplify justice in their daily practices? --